Transmedia mobilization: Agency and literacy in minority productions in the age of spreadable media - Soriano, Cheryll Ruth R. (Animo Repository, 2016)
This article analyzes the transmedia strategies of three ethnic minority activist organizations in the Philippines: Cordillera Peoples Alliance, Tebtebba, and the Moro Islamic Liberation Front. The fieldwork entailed interviews with leaders of these organizations and their media teams, scholars who study these movements, and social commentators. The analysis shows the complexities of identity construction in the age of spreadable media and the importance of transmedia literacy for activists who have to navigate these complexities to effectively advance their cause. © 2016, Published with license by Taylor & Francis.